The Moderating Role of Good Corporate Governance in the Relationship between Intellectual Capital, Green Accounting, and Company Performance - Dian Indriana Tri Lestari; Risti Ulfi Hanifah; Naini Rizka Amalia (Lembaga Riset dan Inovasi Al-Matani, 2026)
This study aims to examine the effect of intellectual capital and green accounting on company performance, with corporate governance as a moderating variable. This research employs panel data from 20 property and real estate companies listed on the Indonesia Stock Exchange during the 2020–2024 period, resulting in 100 observations. The data were analyzed using panel data regression with the Random Effects Model. The results indicate that intellectual capital has a significant negative effect on company performance, while green accounting does not have a significant effect. Simultaneously, intellectual capital and green accounting significantly influence company performance. Furthermore, corporate governance strengthens the relationship between green accounting and company performance but does not moderate the relationship between intellectual capital and company performance. These findings suggest that the utilization of intellectual capital in the observed sector is not yet optimal, and environmental accounting practices have not been able to directly enhance company performance. This study contributes to the literature by providing empirical evidence from emerging markets and highlighting the role of corporate governance in improving the effectiveness of environmental practices.